Customer Purchasing Intention in Saudi Arabia within the Context of Social Media: Conceptual Model - ALnasser, Asem; Bali Mohomed, Anuar Shah; Hj Hassan, Mazlan; Hashim, Haslinda (International Journal of Psychosocial Rehabilitation, 2019)
To investigate the impact of influencer’s credibility on consumer’s intentions to purchase within the context of social media. And the impact of trust and attitude as mediators between social media features such as usability. Methodology: This research was conducted within the social media where Saudi users are commonly known among the top active users in this domain. This study conducted a systematic review of prior studies regarding the intention to purchase online. While investigating various constructs proposed previously in the special case of Saudi Arabia, which has preference to brick-and-mortar stores and appreciation for social media influencers. Main Findings: There is a lack of models that explain consumers’ intention to purchase within the social media context. Much appreciation has been put on influencer’s credibility, yet trust and attitude have been found to have a critical role on consumers' positive intention to purchase within the context of social media among Saudi consumers. Implication: This study spots light on the combination of influencer’s credibility, attitude, and trust in order to explain more the intention to purchase among social media users—particularly in the Saudi context. The context of this study is Saudi social media users who have unique features, such as being the top active users on social media, and there is a quit number of influencers who have millions of followers, and those influencers are involved in many marketing campaigns. Originality of this study: this study investigated purchase intention within social media, particularly in the Saudi context, which is rarely discussed. Moreover, the influencer’s credibility as moderator has not been investigated before